(untitled) (Revista Española de Derecho Internacional, 2022)
In both the European Union and the United States, it is a dynamic period for private international law regarding immovable property issues. The predominant approach has been that these issues are governed by the lex rei sitae —that is, the law of the State where the immovable is located. However, through a comparative examination of recent EU Regulations on succession, matrimonial property regimes, and the property consequences of registered partnerships, and of the new Third Restatement of Conflict of Laws project in the United States, this article shows that on both sides of the Atlantic there is a trend toward reducing the scope of the lex rei sitae rule. It explores both the reasons for and the challenges posed by this trend. It also reveals that despite this trend, the lex rei sitae rule nevertheless persists in relation to certain «core» immovable property issues.